Identification of Salmonella sp. in Milkfish (Chanos chanos) Collected from PPI Ujong Baroh, West Aceh - Ahmad Rasyid Pohan; Sri Wahyuni; Hayatun Nufus; Ismail Sulaiman; Samsul Bahri (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Milkfish (Chanos chanos) is an important fishery commodity in Indonesia due to its high nutritional value and affordability. However, its high moisture and protein content make it highly susceptible to microbial contamination, including pathogenic bacteria such as Salmonella sp., which may pose serious food safety risks to consumers. This study aimed to detect and characterize Salmonella sp. in milkfish landed at the Ujong Baroh Fish Landing Base (PPI Ujong Baroh), West Aceh Regency, Indonesia. The study was conducted in April 2025 using an observational sampling approach followed by laboratory-based microbiological analysis. A total of 10 milkfish samples were collected purposively during fish landings. Samples were aseptically dissected, and tissues from the gills, skin, muscle, and intestine were homogenized for bacterial analysis. Isolation was carried out using Buffer Peptone Water (BPW) as a pre-enrichment medium and Salmonella Shigella Agar (SSA) as a selective medium. Identification was performed based on macroscopic colony morphology and microscopic Gram staining characteristics. The results showed that all ten samples tested positive for Salmonella sp. contamination. Colonies grown on SSA medium exhibited circular shapes, black pigmentation, smooth surfaces, entire margins, and convex elevations. Microscopic observations revealed Gram-negative coccobacillus to be short rod-shaped bacteria that appeared pink after Gram staining. These findings indicate that milkfish landed at PPI Ujong Baroh were contaminated by Salmonella sp., highlighting the need for improved sanitation practices and stricter microbiological monitoring during post-harvest fish handling